(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
The image is one of the most important criteria that critics relied on to reveal the aesthetics of literary texts in general, and poetry in particular, as well as one of the criteria they adopted in balancing poets, and distinguishing good poetry from bad; Therefore, they paid great attention to explaining the concept of the image - ancient and modern - and differed in what is meant by it. the research tried to study the image at its first level (similarity, metaphor and metonymy) in the poetry of Khufaf bin Nudbah Al-Salami.To find out his method in constructing his images and their suitability to the meanings that were given for them and the home of beauty in them. The research concluded that the simile was the most common element in his poetry, because the poet belongs to a civilized phase in which the simile was prevalent, because of its sensuality that fits the nature of the era and society in the pre-Islamic era and the early Islam era.